Watkins Family in Remodeled Kitchen at 3506 E. Balch Avenue - Watkins, Howard::::::::: (1980)
Christine Watkins, Howard Watkins, Adam Watkins standing in remodeled kitchen; all waving Ice door in refrigerator; Trimline telephone 12" BW television